Are head impacts safe during youth soccer game practice? - O'Sullivan, D.; Kwak, M.-H.; Kim, Y.-S; Jeong, H. S. (Korean Journal of Sport Biomechanics, 2020)
Objective: This study to identify the mechanism of head impact that occurs during youth soccer game with regard to head injuries in sports. Method: Ten male subjects (age: 10.0±2.0 yrs.) were participated during 10 soccer practices spread out over a time period of 10 weeks. During each soccer game, the participants agreed and wore the X-Patch (wireless accelerometer, gyroscopes). The X-Patch records the head impact mechanics, such as peak linear acceleration (PLA), peak rotational acceleration (PRA), peak rotational velocity (PRV), Head Injury Criterion (HIC), and the location of impact. Results: A total of 501 impacts to the head were measured over the 10 soccer games, PLA 17.8±10.4 g, PRA 3168±2442 rad/s²; PRV 16.1±10.6 rad/s; HIC 11.7±34.2. The severity of impact was classified into 3 ranges; low 10~39 g (482 impacts); medium 40~69 g (17 impacts); and high >69 g (2 impacts). There are no significant differences in PLA and HIC (p=0.08, p=0.15), however PRA and PRV show the differences (p<.05) between each of the participants. For the analysis comparing between the soccer games, there are no significant differences in PLA, PRA, PRV and HIC (p=0.11, p=0.13, p=0.14, p=0.05). Conclusion: Our results indicated that there were significant differences between athletes, especially in terms of rotational acceleration, whereas there were significant differences in linear and rotational based variable between each of the soccer games. Although the vast majority of impacts were below 39 g there were 2 potentially dangerous impacts above 69 g. It is important that future research continuous to measure head impact mechanics during soccer to help understand head injury mechanisms to ensure the safety of athletes.